2002
DOI: 10.1063/1.1524294
|View full text |Cite
|
Sign up to set email alerts
|

High-efficiency SiO2:Ce3+ glass scintillators

Abstract: We present the effect of a rapid thermal treatment (RTT) at high temperature (1800 °C) on the radio-luminescence properties of Ce-doped SiO2 glasses prepared by the sol–gel method and previously densified at 1050 °C. Cerium concentrations ranging from 0.05 up to 1 mol % were considered. We found that, for all concentrations, the RTT induces a strong increase of the Ce3+ radio-luminescence efficiency; the x-ray-induced luminescence intensity of the SiO2:0.1% Ce is about twice that of Bi3Ge4O12. The decay time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 20 publications
3
64
0
Order By: Relevance
“…Variables in this first phase consisted in doping with different rare earth ions (cerium, europium, gadolinium, terbium, ytterbium) and in variation of sintering conditions for Ce doped sol-gel matrices (either oxidizing or reducing atmosphere ) [22][23][24][25][26][27]. Following these previous tests, further investigation was restricted to Cerium and Europium doping.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Variables in this first phase consisted in doping with different rare earth ions (cerium, europium, gadolinium, terbium, ytterbium) and in variation of sintering conditions for Ce doped sol-gel matrices (either oxidizing or reducing atmosphere ) [22][23][24][25][26][27]. Following these previous tests, further investigation was restricted to Cerium and Europium doping.…”
Section: Resultsmentioning
confidence: 99%
“…Rare earth-doped SiO2 powders were produced by a simple modification of the synthesis published elsewhere to obtain bulk doped-samples [23]. Specifically, the Sol solution is obtained with the following composition: ethanol 99.9% 18 ml; TEOS 6 ml; water 3.6 ml and Ce(Eu)(NO3)3*12· H2O solution in ethanol (10 mg/ml) in the amount needed to obtain the proper level doping in SiO2 (the most effective doping level for Ce and Eu ions is about 600 molar ppm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…30). In (Chiodini et al, 2002) strong increase of scintillation efficiency was reported at Ce-doped silicate glass after RTT treatment. In our case, similar conclusion can be drawn for the highest RTT temperature of 2000 0 C, when the spectrum remains low energy shifted compared to the situation in the powder nanocomposite annealed at 1250-1300 °C (Fig.…”
Section: Luminescent Propertiesmentioning
confidence: 99%
“…Following the procedure carried out at the Ce-doped silicate glasses (Chiodini et al, 2002) the samples of SiO 2 /Lu 2 Si 2 O 7 nanocomposites annealed at 1000°C were rapidly heat-treated at temperature between 1600-2000 °C. This rapid thermal treatment (RTT) consisted of 30 seconds heating period in the hydrogen-oxygen flame.…”
Section: Luminescent Propertiesmentioning
confidence: 99%